A Purified Zinc Protease of Pea Chloroplasts, EP1, Degrades the Large Subunit of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase. - Bushnell, T. P. (1993)
A previously reported endopeptidase (EP1) from pea chloroplasts was purified over 11,000-fold using a four-step protocol involving ultrafiltration, sucrose gradient centrifugation, isoelectric focusing, and high performance liquid chromatography gel filtration. The enzyme was determined to be a metalloprotease requiring bound Zn2+ and added Mg2+ or Ca2+ for proper activity. Its localization in the stroma of pea chloroplasts was confirmed by demonstrating its insensitivity to thermolysin when the envelope was intact. A contaminating serine protease that attacks EP1 was found. The contaminating protease was inhibited by 4-(2-aminoethyl)-benzenesulfonyl fluoride, but not by o-phenanthroline, whereas EP1 sensitivities were the reverse. EP1 is able to hydrolyze the large subunit of native ribulose-1,5-bisphosphate carboxylase/oxygenase under physiological conditions.